Galactosylated iron oxide nanoparticles for enhancing oral bioavailability of ceftriaxone. (16th March 2021) - Kawish, Muhammad; Jabri, Tooba; Elhissi, Abdelbary; Zahid, Hina; Muhammad Iqbal, Kanwal; Rao, Komal; Gul, Jasra; Abdullah, Muhammad; Shah, Muhammad Raza
Abstract: The current study focuses on the development, characterization, biocompatibility investigation and oral bioavailability evaluation of ceftriaxone (CFT)-loaded lactobionic acid (LBA)-functionalized iron oxide magnetic nanoparticles (MNP-LBA). Atomic force microscopy and dynamic light scattering showed that the developed CFT-loaded MNP-LBA is spherical, with a measured hydrodynamic size of 147 ± 15.9 nm and negative zeta potential values (–35 ± 0.58 mV). Fourier transformed infrared analysis revealed interactions between the nanocarrier and the drug. Nanoparticles showed high drug entrapment efficiencies of 91.5 ± 2.2%, and the drug was released gradually in vitro and shows prolonged in vitro stability using simulated gastrointestinal (GI) fluids. The formulations were found to be highly biocompatible (up to 100 µg/mL) and hemocompatible (up to 1.0 mg/mL). Using an albino rabbit model, the formulation showed a significant enhancement in drug plasma concentration up to 14.46 ± 2.5 µg/mL in comparison with its control (1.96 ± 0.58 µg/mL). Overall, the developed MNP-LBA formulation was found promising for provision of high-drug entrapment, gradual drug release and was appropriate for enhancing the oral delivery of CFT.